Transition toward democracy – Georgian problems - Markozashvili, Lasha (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
The process of democratisation in Georgia has its obstacles, mostly connected with cultural and socio-economic aspects. Political challenges are interlinked with societal attitudes and vice versa. The historical role of the Orthodox Church in preserving Georgian national identity throughout the centuries is over-compensated for, with frequent clerical involvements in public life. Non-democratic governments have made no effort to finalise the process of transition and for two decades the state has remained in the grey zone between consolidation and autocracy. 2012 was marked as a year for the new hopes of Georgian democracy, a new government was elected via free and fair elections, but democracy needs conditions to endure and this paper examines those conditions.

Proces demokratyzacji w Gruzji ma swoje trudności, głównie związane z aspektem kulturowym i społeczno-ekonomicznym. Wyzwania polityczne są powiązane z postawą społeczną i odwrotnie. Historyczna rola kościoła prawosławnego w zachowaniu gruzińskiej tożsamości narodowej przez wieki jest nadmiernie kompensowana z częstymi pisarskimi uwikłaniami w życiu publicznym. Niedemokratyczne rządy dokonały wszelkich starań, aby sfinalizować proces transformacji i przez dwie dekady stan pozostawał w szarej strefie między konsolidacją i autokracją. Rok 2012 został oznaczony rokiem dla nowych nadziei demokracji Gruzji. Nowy rząd został wybrany przez wolnych i uczciwych wyborców, ale demokracja wymaga warunków aby przetrwać i ten artykuł je bada.
Tranzycja w kierunku demokracji – problemy Gruzji
Keywords: Georgia; democratic transition; political culture; Saakashvili; Orthodox Church; Gruzja; demokratyczne przemiany; kultura polityczna; Saakaszwili; Kościół Prawosławny